Sociological Realism and the Study of the Relativity of Culture - Leonavičius, Vylius (Problemos, 1987)
The article discusses the methodological relationship between positivistic sociology and the relativistic conceptions of the empirical culturology. The holism or the organistic conception of society has influenced the functionalistic method in the formation of sociology and culturology. Despite of some fallacies (tautology and teleology), the functionalistic method has become the dominant method in American and English culturology. It is argued that the functionalistic method leads to relativism in the study of culture.